1901 Neb. Laws 141 - (:unkn) unknown (My University, 1901)
Ch. 16, § 129, pt. 55: to prevent use of fire arms, rockets, powder, fire works, or other dangerous and combustible material; carrying of concealed weapons; to arrest, punish, fine or set at work on streets or elsewhere vagrants and persons found without visible means of support, or legitimate business; to regulate and prevent the transportation of gun powder
Keywords: CARRY - CONCEALED; DISCHARGE; GUNPOWDER - TRANSPORTATION